BOOK REVIEWS (Journal of Finance, 1974)
Book reviewed in this article: Stabilization Policies in Interdependent Economies . Edited by E mil C laassen and P ascal S alin . Government Spending and Land Values—Public Policy and Private Gain . Edited by C. L owell H arriss . Permanent Income, Wealth and Consumption . By T homas M ayer . Security Evaluation and Portfolio Analysis . Edited by E dwin J. E lton and M artin J. G ruber . The Theory of Finance . By E ugene F. F ama and M erton H. M iller . The Theory of Financial Decisions . By C harles W. H aley and L awrence D. S chall . Mathematical Methods in Investment and Finance . Edited by G. P. S zego and K arl S hell Financial Development and Economic Growth: The Consequences of Underdeveloped Capital Markets . Edited by A rnold S ametz . The International Money Game . By R obert Z. A liber . European Capital Markets: Towards a General Theory of International Investment . By B runo H. S olnik .